Gethok Tular, Pola Komunikasi Gerakan Sosial Berbasis Kearifan Lokal Masyarakat Samin di Sukolilo - Rini Darmastuti; Atwar Bajari; Haryo S Martodirdjo; Eni Maryani (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2016)
The social movement that strongly opposed the construction of cement plant in Sukolilo, Pati, Central Java constitutes a unique social movement. This movement, which is known as protest action, was conducted in a non violent way. One of the ways to embrace people in Sukolilo is by using communication strategy, called as ‘gethok tular’. This is a communication strategy based on local wisdom owned by Samin community. In its growth, gethok tular has formed communication pattern in Samin’s social movement. The communication pattern of gethok tular is in the form of informal communication. This paper was based on the result of constructivist research using ethnography of communication approach. Direct and in-depth interviews were employed to collect data.